2013
DOI: 10.1088/1054-660x/23/6/066004
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared mediated tumor destruction by photothermal effect of PANI-Npin vivo

Abstract: Photothermal therapy is a therapy in which photon energy is converted into heat to kill cancer. The purpose of this study is to evaluate the in vivo efficacy of photothermal therapy, toxicity and hepatic and renal function of polyaniline nanoparticles (PANI-Np) in a tumor-bearing mice model. The in vivo efficacy of nanoparticles, following NIR light exposure, was assessed by examining tumor growth over time compared to the untreated control. Signs of drug toxicity and the histopathology and morphology of tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
1
26
1
Order By: Relevance
“…These results suggest that the combination of nanoparticles and radiation triggers cell death by apoptosis in attached cells. Promising results with these nanoparticles were obtained in our laboratory for in vivo assays with apoptosis and necrosis as the responsible mechanisms of cell death (Ibarra et al 2013). Previous studies of polyaniline nanoparticles in PTT showed similar results in different cancer cell lines (Yang et al 2011;Zhou et al 2013).…”
Section: Laser Treatment Of Tumor Cells With Pani-npsmentioning
confidence: 77%
See 1 more Smart Citation
“…These results suggest that the combination of nanoparticles and radiation triggers cell death by apoptosis in attached cells. Promising results with these nanoparticles were obtained in our laboratory for in vivo assays with apoptosis and necrosis as the responsible mechanisms of cell death (Ibarra et al 2013). Previous studies of polyaniline nanoparticles in PTT showed similar results in different cancer cell lines (Yang et al 2011;Zhou et al 2013).…”
Section: Laser Treatment Of Tumor Cells With Pani-npsmentioning
confidence: 77%
“…However, the major issue with these types of nanomaterials is their low biocompatibility, particularly their long-term toxicity, which limits their clinical application (Balasubramanian et al 2010;Zhang et al 2011). Recently, we have demonstrated that polyaniline nanoparticles are very effective for in vivo photothermal therapy, and have nontoxic effects and a good tolerance (Ibarra et al 2013. Polyaniline is one of the most promising conducting organic polymers because of its low cost, facile synthesis, high conductivity, and environmental and chemical stabilities (Heeger 1993;Stejskal and Sapurina 2005;Stejskal and Proke 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature change is enough to induce cell death of tumoral cells because those cells have a diminished functionality of the DNS repair systems, correlated with its increased growth rate. Indeed, it has been shown that excellent photothermal therapy efficacy is achieved in-vivo upon intratumoral injection of PANI NPs followed by nearinfrared light exposure [35]. The results suggested that PANI NPs could be considered as an effective photothermal agent and pave the way to future cancer therapeutics.…”
Section: Photothermal Effect By Near Infrared Radiation Absorptionmentioning
confidence: 99%
“…In a variety of research fields involving PTT, the design and development of PTT agents with tissue‐transparent near‐infrared (NIR) absorption properties has attracted widespread interest, which is important for achieving future clinical implementation . Currently available PTT agents mainly include two types of nanomaterials: inorganic nanomaterials, such as Cu‐, Au‐,[4b,8] Pd‐, carbon‐based nanomaterials, as well as a few others, and organic conjugated polymer‐based nanomaterials, such as polyaniline (PANI)‐, polypyrrole‐, polythiophene‐, and polydopamine‐based nanoparticles . Recently, inorganic nanomaterial‐based PTT agents have been utilized to photoablate melanoma .…”
Section: Introductionmentioning
confidence: 99%